Antiparasitic Efficacy of Curcumin Against Besnoitia besnoiti Tachyzoites in vitro - Cervantes-Valencia, María Eugenia; Hermosilla, Carlos; Alcalá-Canto, Yazmín; Tapia, Graciela; Taubert, Anja; Silva, Liliana M. R. (Frontiers in Veterinary Science, 2019)
Besnoitia besnoiti is the causative agent of bovine besnoitiosis. B. besnoiti infections lead to reduced fertility and productivity in cattle causing high economic losses, not only in Europe, but also in Asia and Africa. Mild to severe clinical signs, such as anasarca, oedema, orchitis, hyperkeratosis and characteristic skin and mucosal cysts, are due to B. besnoiti tachyzoite and bradyzoite replication in intermediate host tissues. So far, there are no commercially available effective drugs against this parasite. Curcumin, a polyphenolic compound from Curcuma longa rhizome is well-known for its antioxidant, anti-inflammatory, immunomodulatory and also anti-protozoan effects. Hence, the objective of this study was to evaluate the effects of curcumin on viability, motility, invasive capacity and proliferation of B. besnoiti tachyzoites replicating in primary bovine umbilical vein endothelial cells (BUVEC) in vitro. Functional inhibition assays revealed that curcumin treatments reduce tachyzoite viability and induce lethal effects in up to 57% of tachyzoites (IC50 in 5.93 µM). Referring to general motility, significant dose-dependent effects of curcumin treatments were observed. Interestingly, curcumin treatments only dampened helical gliding and twirling activities whilst longitudinal gliding motility was not significantly affected. In addition, curcumin pretreatments of tachyzoites resulted in a dose-dependent reduction of host cell invasion as detected by infections rates at one day p. i. These findings demonstrate feeding cattle with Curcuma longa rhizomes may represent a new strategy for besnoitiosis treatment.